Excess Ground Ice Profiles in Continuous Permafrost Mapped From InSAR Subsidence - S. Zwieback; G. Iwahana; S. Sakhalkar; R. Biessel; S. Taylor; F. J. Meyer (Water Resources Research)
Abstract Excess ground ice formation and melt drive surface heave and settlement, and are critical components of the water balance in Arctic soils. Despite the importance of excess ice for the geomorphology, hydrology and biogeochemistry of permafrost landscapes, we lack fine‐scale estimates of excess ice profiles. Here, we introduce a Bayesian inversion method based on remotely sensed subsidence. It retrieves near‐surface excess ice profiles by probing the ice content at increasing depths as the thaw front deepens over summer. Ice profiles estimated from Sentinel‐1 interferometric synthetic aperture radar (InSAR) subsidence observations at 80 m resolution were spatially associated with the surficial geology in two Alaskan regions. In most geological units, the estimated profiles were ice poor in the central and, to a lesser extent, the upper active layer. In a warm summer, units with ice‐rich permafrost had elevated inferred ice contents at the base of the active layer and the (previous years') upper permafrost. The posterior uncertainty and accuracy varied with depth. In simulations, they were best (≲0.1) in the central active layer, deteriorating (≳0.2) toward the surface and permafrost. At two sites in the Brooks Foothills, Alaska, the estimates compared favorably to coring‐derived profiles down to 35 cm, while the increase in excess ice below the long‐term active layer thickness of 40 cm was only reproduced in a warm year. Pan‐Arctic InSAR observations enable novel observational constraints on the susceptibility of permafrost landscapes to terrain instability and on the controls, drivers and consequences of ground ice formation and loss.